Genome-Wide Detection of CNVs and Association With Body Weight in Sheep Based on 600K SNP Arrays - Wang, Zhipeng; Guo, Jing; Guo, Yuanyuan; Yang, Yonglin; Teng, Teng; Yu, Qian; Wang, Tao; Zhou, Meng; Zhu, Qiusi; Wang, Wenwen; Zhang, Qin; Yang, Hua (Frontiers in Genetics, 2020)
Copy number variations (CNVs) are important structural variations, and can give rise to significant phenotypic diversity. Herein, we used high-density 600K SNP arrays to detect CNVs in two synthetic lines of sheep (DS and SHH) and in Hu sheep (a local Chinese breed). A total of 919 CNV regions (CNVRs) were detected with a total length of 48.17Mb, accounting for 1.96% of the sheep genome. These CNVRs consisted of 730 gains, 102 losses, and 87 mixed. We found that these CNVRs were significantly enriched in the Segmental duplication (SD) region. Cluster analysis of three breeds based upon CNVRs revealed that the DS and SHH breeds shared a close genetic relationship. Functional analysis revealed that some genes in these CNVRs were also significantly enriched in the olfactory transduction pathway (oas04740), including certain members of OR gene family such as OR6C76, OR4Q2, and OR4K14. According to association analyses and previous gene annotation, we determined that some highlight genes were likely to be associated with body weight, including FOXF2, MAPK12, MAP3K11, STRBP and C14orf132. Together these results offer valuable information that will guide future association studies aimed at exploring the genetic basis for body weight in sheep.